Upgrading higher pharmaceutical education by actualizing a competence approach - Nafiset Maskhudovna Bat; Fatima Shumafovna Siyukhova; Galina Vladimirovna Kadakoeva (Вестник Майкопского государственного технологического университета)
Continuous improvement and modernization of higher education educational programs that meet the requirements of modern pharmaceutical industry, correlated with the quality training of highly qualified pharmaceutical personnel, predetermines the progressive dynamics of the pharmaceutical industry in the Russian Federation. The introduction of the new regulatory documentation into the practice of Russian higher education institutions has led not only to a conceptually new approach to regulating the educational process in the specialty “Pharmacy”, but also created the prerequisites for constructing a meaningful pyramid of professional competencies of a specialist of this field. The relevance of the research topic is due to the need to comply with the competence content of educational programs implemented in the “Pharmacy” specialty, with the requirements of business entities in the pharmaceutical industry for graduates of this field, taking into account adaptation of international standards to the realities of the domestic pharmaceutical industry. Today great importance is attached not only to the theoretical training of pharmacists, but also to the sustainable formation of their professional competencies. An important problem is the alignment of the content of educational programs developed and implemented by higher education institutions in terms of their competence-based content with the main trends in Russian pharmaceutical education. The following research methods were used: a formalized method for analysis, analysis of regulatory and methodological documents, an epistemological method. Conceptually new provisions that determined changes in the development of work programs in the disciplines of the pharmaceutical focus have been studied. A more professionally oriented approach has been revealed regarding general educational disciplines including replacing general cultural competencies with universal ones; increase regulation of the results of mastering the discipline and ways of achieving them (introduction of achievement indicators).